Tuberculosis stigma as a social determinant of health: a systematic mapping review of research in low incidence countries. (March 2017) - Craig, G.M.; Daftary, A.; Engel, N.; O'Driscoll, S.; Ioannaki, A.
Highlights: Tuberculosis (TB) related stigma is an important social determinant of health that can impact health-seeking practices and illness management. Research on TB stigma has been conducted predominantly in high incidence countries. This study aimed to map research in low burden settings. Few studies included stigma as a substantive topic or theorized stigma as a social determinant of health. Future research on stigma would benefit from a stronger theoretical underpinning including the intersection with the social determinants. Summary: Tuberculosis (TB)-related stigma is an important social determinant of health. Research generally highlights how stigma can have a considerable impact on individuals and communities, including delays in seeking health care and adherence to treatment. There is scant research into the assessment of TB-related stigma in low incidence countries. This study aimed to systematically map out the research into stigma. A particular emphasis was placed on the methods employed to measure stigma, the conceptual frameworks used to understand stigma, and whether structural factors were theorized. Twenty-two studies were identified; the majority adopted a qualitative approach and aimed to assess knowledge, attitudes, and beliefs about TB. Few studies included stigma as a substantive topic. Only one study aimed to reduce stigma. A number of studies suggested that TB control measures and representations of migrants in the media reporting of TB were implicated in the production of stigma. The paucity of conceptual models and theories about how the social and structural determinants intersect with stigma was apparent. Future interventions to reduce stigma, and measurements of effectiveness, would benefit from a stronger theoretical underpinning in relation to TB stigma and the intersection between the social and structural determinants of health.